Bidirectional effects on interhemispheric resting‐state functional connectivity induced by excitatory and inhibitory repetitive transcranial magnetic stimulation. Issue 5 (29th July 2013) - Watanabe, Takamitsu; Hanajima, Ritsuko; Shirota, Yuichiro; Ohminami, Shinya; Tsutsumi, Ryosuke; Terao, Yasuo; Ugawa, Yoshikazu; Hirose, Satoshi; Miyashita, Yasushi; Konishi, Seiki; Kunimatsu, Akira; Ohtomo, Kuni
Abstract Several recent studies using functional magnetic resonance imaging (fMRI) have shown that repetitive transcranial magnetic stimulation (rTMS) affects not only brain activity in stimulated regions but also resting‐state functional connectivity (RSFC) between the stimulated region and other remote regions. However, these studies have only demonstrated an effect of either excitatory or inhibitory rTMS on RSFC, and have not clearly shown the bidirectional effects of both types of rTMS. Here, we addressed this issue by performing excitatory and inhibitory quadripulse TMS (QPS), which is considered to exert relatively large and long‐lasting effects on cortical excitability. We found that excitatory rTMS (QPS with interstimulus intervals of 5 ms) decreased interhemispheric RSFC between bilateral primary motor cortices, whereas inhibitory rTMS (QPS with interstimulus intervals of 50 ms) increased interhemispheric RSFC. The magnitude of these effects on RSFC was significantly correlated with that of rTMS‐induced effects on motor evoked potential from the corresponding muscle. The bidirectional effects of QPS were also observed in the stimulation over prefrontal and parietal association areas. These findings provide evidence for the robust bidirectional effects of excitatory and inhibitory rTMSs on RSFC, and raise a possibility that QPS can be a powerful tool to modulate RSFC. Hum Brain Mapp 35:1896–1905, 2014. © 2013 Wiley Periodicals, Inc.